Depiction of Ishana on the Kakshasana of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Ishana is portrayed, on the kakshasana (seat back) of the Undeshwar Temple, with four arms, carrying a trishula (trident) and a sarpa (snake) in his upper hands. In his lower hands, he holds a kamandalu (water pot) and extends a varadaksha (giving blessing) gesture. Adorned with a jatamukuta (crown of matted hair) and jewelry, his vehicle, the bull, is depicted at the bottom right.